Sputtering of tungsten exposed to high-flux and high-fluence hydrogen ion beam - Bizyukov, I.A. (Вопросы атомной науки и техники, 2013)
Tungsten samples were irradiated by hydrogen ion beam with high heat (0.1…1.05 MW·m⁻²) and particle [(0.13…1.3)×10²² m⁻²s⁻1] flux generated by FALCON ion source. The sputtering yield has remained nearly constant in the given flux range. Scanning electron microscope (SEM) studies of the irradiated surface have indicated that the only influence of the ion beam in the fluence range up to 2.6×10²⁶ m⁻² is the increase of roughness. Зразки вольфраму опромінювалися пучком іонів водню з високою щільністю частинок [(0.13…1.3)×1022 м⁻²с⁻¹] і потужністю (0.1…1.05 МВт·м⁻²), який генерувався іонним джерелом FALCON. Коефіцієнт розпилення залишався приблизно постійним в заданому діапазоні щільності іонних потоків. Вивчення поверхні з допомогою РЕМ показало, що вплив пучка на поверхню призводить лише до збільшення шорсткості в діапазоні флюенсів <2.6×10²⁶ м⁻². Образцы вольфрама облучались пучком ионов водорода с высокой плотностью частиц [(0.13…1.3)×10²² м⁻²с⁻1] и мощностью (0.1…1.05 МВт·м⁻²), который генерировался ионным источником FALCON. Коэффициент распыления оставался приблизительно постоянным в заданном диапазоне плотности ионных потоков. Изучение поверхности с помощью РЭМ показало, что воздействие пучка на поверхность приводит только лишь к увеличению шероховатости в диапазоне флюенсов < 2.6×10²⁶ м⁻².